PERAN KEPUASAN KERJA MEMEDIASI PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN PT. INDOCITRA JAYA SAMUDERA JEMBRANA BALI - Wiyatanti, Adinda Putri; Ketut Netra, I Gusti Salit (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.12.TAHUN.2022DO - 10.24843/EEB.2022.v11.i12.p13, 2022)
Human resource management is a must if an organization wants to develop and compete with other organizations. Organizations need to pay attention to employee organizational citizenship behavior, because organizational citizenship behavior is very important to support the effectiveness of organizational functions. This study aims to analyze the role of job satisfaction in mediating the effect of perceived organizational support on organizational citizenship behavior of employees of PT. Indocitra Jaya Samudera. The number of samples in this study were 116 respondents with the method of determining saturated sampling. Collecting data through interviews and distributing questionnaires. The data were analyzed using path analysis techniques. The results showed that perceived organizational support had a positive and significant effect on organizational citizenship behavior, perceived organizational support had a positive and significant effect on job satisfaction, job satisfaction had a positive and significant effect on organizational citizenship behavior, job satisfaction had a partial role in mediating the effect of perceived organizational support on organizational citizenship behavior.